THE EFFECT OF INFORMATION TECHNOLOGY USAGE INTENSITY AND TECHNOLOGICAL COMPETENCE ON GENERATION Z LEADERSHIP EFFECTIVENESS THROUGH TEAMWORK (Evidence from Junior Chamber International Indonesia) - Sanda Risma Panggabean; Zainul Kisman (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2026)
The rapid advancement of information technology has reshaped leadership practices, particularly among Generation Z as digital natives. However, empirical evidence remains inconclusive regarding whether leadership effectiveness is driven by the intensity of technology usage or by technological competence, especially within non-profit youth organizations. This study aims to examine the effect of information technology usage intensity and technological competence on Generation Z leadership effectiveness, with teamwork as a mediating variable. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (PLS-SEM). Data were collected from 59 Generation Z members (aged 18–29) of Junior Chamber International (JCI) Indonesia. The results reveal that technology usage intensity does not significantly affect leadership effectiveness or teamwork. In contrast, technological competence has a significant positive effect on teamwork, which in turn significantly influences leadership effectiveness. Teamwork fully mediates the relationship between technological competence and leadership effectiveness. These findings indicate that Generation Z leadership effectiveness is not determined by how frequently technology is used, but by how technological competence is strategically leveraged to foster collaboration and teamwork. This study contributes to digital leadership literature by highlighting teamwork as a critical mechanism linking technological competence to leadership effectiveness in youth-based non-profit organizations.